Considerações de uma estudante de terapia ocupacional para uma prática profissional inclusiva, ecológica e integral - Porto, Julia Caltabiano (Universidade Federal de São Carlos, 2020)
It is a systematization of the experience of a graduate student in occupational therapy, from acting in several extension projects with popular education in health and complementary therapies. Objective: to analyze the possible convergences between the fields of knowledge of popular education in health and complementary therapies with occupational therapy. Method: followed the referential of the systematization of experiences that, from the structuring and reconstruction, shows the logic of the lived process, the factors that occurred in the process, how and why they were related, through dialectical analysis. Experiences between 2015 and 2020 were selected and reflections and interpretations were developed based on learning. Results and discussion: the experiences with integrative vibrational therapy and popular health education practices were highlighted and correlated with the themes and graduation routine in occupational therapy. Working in groups, building solutions and dialogues in a collaborative way, the character of social inclusion and the critical and decolonial reflective perspective, were common aspects highlighted in the experience, being addressed themes of public policies, social context, human rights, solidary economy, ecology occupational, community and integrative practices for health promotion. Conclusions: the construction of an inclusive, ecological and integral occupational therapy practice based on the benchmarks of complementary therapies and popular health education follows a convergent direction towards interdisciplinarity, humanization, sustainability, inclusion, autonomy, quality of life and enhancement of knowledge and beings. The systematization of the experience enabled the expression of thoughts and wishes for future professional practice.
Considerations of an occupational therapy student for an inclusive, ecological and integral professional practice
Keywords: Terapia ocupacional; Educação popular em saúde; Terapias complementares; Sistematização de experiências; Práticas interdisciplinares; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL